Penentuan Kawasan Kebisingan Bandara Adi Sucipto Yogyakarta - Muliasari, Ataline (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
Density rate of arrival and departu re of nircmft would cnuse noise pollution and air area of the airport.Meanwhile, the intemational demands the maintenance of environmental conditions in the world.For people wlw live near the airport will certainly feel uncomfortable and unhealthy. !CAO (InternationalCivil Aviation Organiza.tion) as the agenct; responSible for civil mnation is clearly not turninga blind (!l;e on this. Thus enforcing the regulations limiting noise/ noise limit. Until now, the area ofairport noise is determined based on forecasts of nircmft, frequency and period of ti1ne aircraft operations.From the analysis shows tlmt tlze Adi Sucipto Airport i11 Yogynknrtn Juzs n noise level WECPNL115.371 .